2011
DOI: 10.1007/s10899-011-9281-x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Vulnerability and Problem Gambling: An Application of Durand Jacobs’ General Theory of Addictions to Electronic Gaming Machine Playing in Australia

Abstract: The aim of this study was to conduct an empirical investigation of the validity of Jacobs' (in J Gambl Behav 2:15-31, 1986) general theory of addictions in relation to gambling problems associated with electronic gaming machines (EGM). Regular EGM gamblers (n = 190) completed a series of standardised measures relating to psychological and physiological vulnerability, substance use, dissociative experiences, early childhood trauma and abuse and problem gambling (the Problem Gambling Severity Index). Statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 45 publications
7
22
0
Order By: Relevance
“…More specifically, they show that CSA is associated with probable pathological gambling, which has also been found in studies among Inuit (Larsen et al, 2013) as well as non-Indigenous Peoples (Felsher et al, 2010;Hodgins et al, 2010;McCormick et al, 2012). Although there is an abundant literature on the residential school legacy (e.g., see AHF, 2001;RCAP, 1996), few quantitative studies have been conducted on the outcomes of residential schooling, including pathological gambling (Hewitt et al, 1994, but not in Auger & Hewitt, 2000, substance abuse (Corrado & Cohen, 2003), and mental health problems (Corrado & Cohen, 2003).…”
Section: Variablesupporting
confidence: 65%
See 3 more Smart Citations
“…More specifically, they show that CSA is associated with probable pathological gambling, which has also been found in studies among Inuit (Larsen et al, 2013) as well as non-Indigenous Peoples (Felsher et al, 2010;Hodgins et al, 2010;McCormick et al, 2012). Although there is an abundant literature on the residential school legacy (e.g., see AHF, 2001;RCAP, 1996), few quantitative studies have been conducted on the outcomes of residential schooling, including pathological gambling (Hewitt et al, 1994, but not in Auger & Hewitt, 2000, substance abuse (Corrado & Cohen, 2003), and mental health problems (Corrado & Cohen, 2003).…”
Section: Variablesupporting
confidence: 65%
“…These results suggest that CSA may be more prevalent in pathological gambler populations than in the general population, where approximately 20% of women and 10% of men report CSA (Pereda, Guilera, Forns, & Gòmez-Benito, 2009;Stoltenborgh, Van IJzendoorn, Euser, & Bakermans-Kranenburg, 2011;Tourigny, Hébert, Joly, Cyr, & Baril, 2008). Some recent studies also indicate an association between CSA experiences and pathological gambling (Felsher, Derevensky, & Gupta, 2010;Hodgins et al, 2010;McCormick, Delfabbro, & Denson, 2012), although this relationship was not confirmed in others (Fleming, Mullen, Sibthorpe, & Bammer, 1999;Pérez-Fuentes et al, 2013). Moreover, although the causal chain between CSA and gambling is yet to be ascertained, one study has suggested that sexual trauma can cause emotional vulnerability, which in turn increases gambling behaviors (Blaszczynski & Nower, 2002).…”
Section: Sexual Abuse and Gamblingmentioning
confidence: 83%
See 2 more Smart Citations
“…Forms of strain experienced during childhood/adolescence thus warrant attention in future gambling research, as indicated by Durand Jacob's general theory of addictions and its empirical extension to addictive gambling behavior (McCormick, Delfabbro, & Denson, 2012). This theory recognizes childhood life stressors as antecedents to adult problem gambling that predispose individuals to develop psychological vulnerabilities and pursue dissociative experiences (as a form of escape from intolerable mood states) through gambling.…”
Section: Discussionmentioning
confidence: 99%